Glycemic responses of special rice: Case study in Thai geographical indication rice cultivars - Lerdluksamee, Chutima; Srikaeo, Wararat; Srikaeo, Khongsak (Agriculture and Natural Resources, 2024)
Importance of the work: Thai geographical indication (GI) rice cultivars which are special rice types, have not been evaluated for their glycemic responses. Objectives: This study aimed to determine the glycemic indices and glycemic loads of 10 rice varieties registered as Thai GI rice. Materials & Methods: The 10 Thai GI rice varieties; Kum Lanna, Rai Leum Pua Petchabun, Kalasin Kaowong, Hom Mali (Phayao, Thung Kula Rong-Hai and Surin), Leuang Patew Chumphon, Rai Dawk Kha Phangnga, Sangyod Muang Phatthalung, and Jek Chuey Sao Hai were analyzed for their glycemic responses using the standard in vivo method. Results: It was found that Thai GI rice varieties exhibited medium to high glycemic indices and all samples showed high glycemic load values (>20). The glycemic indices ranged from 62.3 (Sangyod Muang Phatthalung) to 82.3 (Kalasin Kaowong). Glycemic indices were discovered to be primarily impacted by variety rather than geography. Main finding: This study was the first to report the glycemic indices of 10 Thai GI rice cultivars and updated the glycemic index database of special rice types, allowing consumers to select healthier rice varieties, such as ones with medium glycemic indices.